Experimental investigation of the influence of an orifice plate on the pressure pulsation amplitude in the pulsating flow in a straight pipe - Rydlewicz, Wojciech; Rydlewicz, Maciej; Pałczyński, Tomasz (Mechanical systems and signal processing, 2019)
[Display omitted] •Pipe characteristic was based on experimental results approximated by a dynamic model.•Downstream influence of orifice plates on pressure pulsation was quantified.•Orifice plates aperture ratio and pressure pulsation relationship was established.•1D acoustic model was confirmed to reliably estimate resonant frequencies of pipes. This paper presents the results of experimental study on the influence of an orifice plate on the levels of pressure pulsation downstream, in the conditions of pulsating flow in the object of research (a straight pipe). The impact of an orifice plate on the pressure pulsation levels was quantified. A decrease in the pressure pulsation level with a decrease in the cross-sectional area of an orifice plate (therefore, a decrease of its aperture ratio - β coefficient) was observed, indicating the usability of this element of piping systems to attenuate pressure pulsations. Experimental data were analysed using a dynamic model of the pipe in software developed in the MATLAB programming environment. The experimental results also indicated the values of the resonant frequencies of the pipe. These were subject to cross-check against a theoretical one-dimensional acoustic model, which may be used to define the natural frequencies of such pipes. According to this model disturbances in working fluid travel at the speed of sound. Compliance of the results of the experiment with the model authenticated the outcomes of the experiment. Moreover, it confirmed that the application of a one-dimensional acoustic model to estimate the resonant frequencies of a straight pipe is a reasonable approach.